Reimagining Brazilian Television: Luiz Fernando Carvalho's Contemporary Vision - Carter, Eli Lee (Latino and Latin American profiles, 2018)
The Brazilian television industry is one of the most productive and commercially successful in the world. At the forefront of this industry is TV Globo and its production of standardized telenovelas, which millions of Brazilians and viewers from over 130 countries watch nightly. Eli Lee Carter examines the field of television production by focusing on the work of one of Brazil's greatest living directors, Luiz Fernando Carvalho. Through an emphasis on Carvalho's thirty-plus year career working for TV Globo, his unique mode of production, and his development of a singular aesthetic as a reaction to the dominant telenovela genre, Carter sheds new light on Brazilian television's history, its current state, and where it is going--as new legislation and technology push it increasingly toward a post-network era.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)